2016
DOI: 10.1097/ccm.0000000000001481
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Mental Health in Trauma Intensive Care Patients

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link Conflicts of Interest and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Length of follow-up was consistent for all study participants in all but two studies [25,26,56]. The same results were found regarding whether follow-up time was sufficient for measuring primary outcomes, with only two studies reporting an insufficient follow-up period [24,47].…”
Section: Quality Of Studiessupporting
confidence: 68%
See 1 more Smart Citation
“…Length of follow-up was consistent for all study participants in all but two studies [25,26,56]. The same results were found regarding whether follow-up time was sufficient for measuring primary outcomes, with only two studies reporting an insufficient follow-up period [24,47].…”
Section: Quality Of Studiessupporting
confidence: 68%
“…Out of the 44 articles that were included in our systematic review, most (n = 12) reported findings from a single prospective cohort study conducted in New Zealand [14, 27-37]. Seven articles were published using data from Australia [24][25][26][39][40][41][42], with two articles related to the same study cohort from Victoria [41,42] and two articles related to the same cohort from South-East Queensland [25,26]. Five articles reported on five unique studies conducted in the United States [38,53,57,64,65].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The possible explanations might be that patients' worries about their disease would added to their psychological burden. In addition, previous research also suggested that patients' illness perception was associated with their mental distress and mental health outcome (Aitken et al, 2016). Regression analysis showed that the disease duration and levels of inflammatory markers were two factors related to self-perceived illness severity.…”
Section: Tablementioning
confidence: 86%
“…This may be explained as follows: First, in the five eligible studies, the shortest intervention time was 20 weeks, and the longest one was only 36 weeks. So the results may be restricted for the dimensions of physical function and social function, which may generate a positive effect for a long‐term intervention (Aitken et al., ). Therefore, for future related studies, our review suggested that the intervention time should be more than 1 year.…”
Section: Discussionmentioning
confidence: 99%